Mini Forklift Design with A Maximum Capacity of 5 Kg - Muhammad Zulfan (International Journal of Mechanical Computational and Manufacturing Research, 2022)
During the long-term development until now, industrial machinery products have shown very rapid progress, both in terms of volume and variety of products produced. The development of this product is not only marked by the fulfillment of public interest, but also leads to the ability to enter exports to increase the country's foreign exchange. In making this mini forklift, the author first understands the methods in planning in the preparation stage and in theory, namely by analyzing the design, because planning also requires the ability to analyze planning to get performance on this mini forklift. In its use in mini forklifts, the shaft is used as a transmission link from the gear motor to the elevator wire. The output power (P) is 0.012 kW. Shaft material is estimated from S30C carbon steel with tensile strength (σ B ) 48 kg/mm2 and shaft rotation is n 105 rpm. With a 1 then the construction of the fork is safe. Based on the calculations and planning carried out, the conclusions are as follows (1) Planning Specifications. a. Material to be lifted: Unit load crates, pipes, iron, cardboard and plates. b. Machine capacity: 5 kg. c. Transmission system: Steel Rope and Pully